Toxic waste - Hunt, Roderick (Gloucester Press, 1998)
The books are designed to look like popular novels for older children with a spine and chapters, boosting confidence and interest of those who may have been stuck on reading scheme books aimed at younger children and appealing to the most image-conscious pupils. This book is also available as part of a mixed pack of 6 different books or a class pack of 36 books